▾ Securon SR: sustained-release verapamil. Issue 12 (15th June 1987) - Unknown
Abstract : Verapamil was the first calcium antagonist in clinical use and its value in the treatment of angina, hypertension and cardiac arrhythmias is well established. 1 Standard verapamil tablets have to be taken twice or three times daily but now a scored sustained-release (s/r) tablet containing 240mg verapamil (Securon SR - Knoll) has been licensed for the treatment of mild to moderate hypertension. A single dose is claimed to lower blood pressure for 24 hours. As we have noted before, 2 the pros and cons of s/r products need careful assessment.